Assessment of Surface Structure of Machined Surfaces - Dobrocky, David; Studeny, Zbynek; Pokorny, Zdenek; Joska, Zdenek; Faltejsek, Petr (Manufacturing Technology Journal, 2019)
This paper deals with basic methodology of surface evaluation of functional surfaces, which were prepared by various machining methods (turning, milling and grinding). Here are the basic 2D (profile) parameters and 3D (spatial) parameters and their properties in relation to the machined surface. Parameters of machined surfaces were obtained by CCI Lite Coherence Correlation Interferometer from Taylor Hobson and evaluated using the TalyMap Platinum software. The article further demonstrates the inappropriateness of the surface structure assessment with only the parameter Ra (mean arithmetic deviation of the profile), which is the most common method in technical practice. This methodology extends the possibilities of a comprehensive assessment of exposed surfaces of machine parts.
Keywords: Surface; structure; microgeometry; profile parameters; machining